2023
DOI: 10.3389/fimmu.2023.1309751
|View full text |Cite
|
Sign up to set email alerts
|

Effects of externally-applied, non-pharmacological Interventions on short- and long-term symptoms and inflammatory cytokine levels in patients with knee osteoarthritis: a systematic review and network meta-analysis

Zhen Wang,
Hui Xu,
Zheng Wang
et al.

Abstract: BackgroundWith the continuous development of clinical medicine, an increasing number of non-pharmacological interventions have been applied for the treatment of knee osteoarthritis (KOA), with the results of several recent randomized controlled trials (RCTs) showing that a variety of externally-applied, non-pharmacological interventions (EANPI) can improve symptoms and inflammation in patients with KOA. However, the relative benefits and disadvantages of non-drug therapies remain uncertain, and an optimal trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…At the deep layer is the vertebral artery. Studies have shown that electroacupuncture at the Fengchi and other points not only relieves the vertigo symptoms of patients with vertigo but also improves the blood flow of the vertebrobasilar artery, and the clinical effect is substantial[ 5 ]. Other studies have reported that cervical Jiaji acupuncture combined with the Fengchi, Hou Xi, and Shu gu points can relieve the symptoms of patients with vertigo, and these mechanisms may be related to the acceleration of the blood flow of the vertebrobasilar artery[ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the deep layer is the vertebral artery. Studies have shown that electroacupuncture at the Fengchi and other points not only relieves the vertigo symptoms of patients with vertigo but also improves the blood flow of the vertebrobasilar artery, and the clinical effect is substantial[ 5 ]. Other studies have reported that cervical Jiaji acupuncture combined with the Fengchi, Hou Xi, and Shu gu points can relieve the symptoms of patients with vertigo, and these mechanisms may be related to the acceleration of the blood flow of the vertebrobasilar artery[ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, IL-4 may contribute to the risk of developing vitiligo. Studies have shown that changes in cytokine levels caused by targeted therapies alter disease symptoms ( 63 , 64 ). Our results provide insight into further understanding the mechanisms of chronic skin inflammation and offer new targets and strategies for the prevention and treatment of immunoinflammatory dermatoses.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated the potential benefits of Tuina for conditions such as lumbar disc herniation, 6 non-specific chronic neck pain 7 and knee osteoarthritis. 8 These effects may be attributed to mechanisms such as inflammation reduction, circulation enhancement and nerve function stimulation. [9][10][11] However, there is currently a shortage of clinical trials observing the effectiveness of Tuina on NSCLBP.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%